Validation of the Portuguese version of the RDC/TMD Axis II questionnaire Validação do questionário RDC/TMD Eixo II em português - Luciana Barbosa Sousa de Lucena; Maurício Kosminsky; Lino João da Costa; Paulo Sávio Angeiras de Góes (Sociedade Brasileira de Pesquisa Odontológica, 2006)
The present paper aimed at evaluating the validity of the Portuguese version of the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) Axis II Questionnaire. The sample was comprised of 155 patients with signs and symptoms of Temporomandibular Disorders (TMD), evaluated at the Orofacial Pain Control Center, School of Dentistry, University of Pernambuco, Brazil, between July 2003 and February 2004. Data collection was performed with the following tools: the RDC/TMD Axis I (clinical evaluation and TMD classification), and Axis II (psychosocial evaluation), as well as specific questionnaires for evaluation of Oral Health Related Quality of Life, namely, Oral Impacts on Daily Performances and the Oral Health Impact Profile-14, considered to be gold standard criteria. Validity evaluation consisted of internal consistency evaluation by the Cronbach alfa reliability test, reliability and reproducibility estimated by the Kappa test and the Spearman's correlation, and concurring validation through Spearman's correlation. The Portuguese version of the RDC/TMD Axis II questionnaire was considered consistent (Cronbach alfa = 0.72), reproducible (Kappa values from 0.73 to 0.91, p < 0.01), and valid (p < 0.01). It was concluded that this version showed valid and reproducible results for the Brazilian population, thus paving the way for including Brazil in transcultural epidemiological studies on TMD. O presente trabalho objetivou avaliar a validade da versão em português do questionário Eixo II dos Critérios Diagnósticos de Pesquisa em Disfunção Temporomandibular (RDC/TMD). A amostra foi composta por 155 pacientes com sinais e sintomas de disfunção temporomandibular (DTM) atendidos no Centro de Controle da Dor Orofacial da Faculdade de Odontologia da Universidade de Pernambuco, Brasil, no período de julho de 2003 a fevereiro de 2004. Para a coleta de dados foram utilizados os seguintes instrumentos: RDC/TMD Eixo I, para avaliação clínica e classificação da DTM, Eixo II, para avaliação psicossocial, e os questionários específicos para avaliação da qualidade de vida relacionada à saúde bucal: Impacto da Saúde Bucal nas Atividades Diárias e Perfil do Impacto na Saúde Bucal-14, considerados padrões-ouro. A validação consistiu na avaliação da consistência interna pelo teste de confiabilidade alfa Cronbach, confiabilidade e reprodutibilidade estimadas pela estatística Kappa e correlação de Spearman e validação concorrente, mediante correlação de Spearman. A versão em português do questionário Eixo II do RDC/TMD foi considerada consistente (alfa Cronbach = 0,72), reprodutível (valores de Kappa entre 0,73 e 0,91; p < 0,01) e válida (p < 0,01). Conclui-se que o instrumento em estudo mostrou-se reprodutível e válido para a população brasileira, possibilitando, assim, a inclusão do Brasil em estudos epidemiológicos transculturais em disfunção temporomandibular.